Correlation-regression analysis of modelled chlorine residual's spatial variability in water supply network - Sanja Marčeta; Dušan Prodanović (Zaštita Materijala)
Residual chlorine ex. concentration of free chlorine disinfection able to carry disinfection in drinking water is an important parameter of drinking water, primarily talking about its bacteriological safety. On the other hand, the presence of free chlorine is a prerequisite for the Trihalomethane's (THM) formation. From this point of view the water quality request for minimum chlorinated and safe potable water is understandable. In numerable modeling and experimental research the spatial diversity of chlorine residual was found to correlate with the daily consumption schedule, the water temperature, the initial dose of chlorine and organic matter content in the water. This paper presents some of the possibilities in predicting the content of residual chlorine and THM in water distribution networks. Special attention is paid to the spatial variability of residual chlorine and THM's to a change in the initial concentration of chlorine. Results are presented using existing water supplying network of the settlement Petrovac na Mlavi using EPANET simulation software.